Cyclocanna producta Peter Schuchert & Aino Hosia & Lucas Leclère 2017, n. comb. - Peter Schuchert; Aino Hosia; Lucas Leclère (Zenodo, 2017)
Cyclocanna producta (G.O. Sars, 1874) n. comb. Fig. 7 Cyclocanna welshi Bigelow, 1918: 384, pl. 3 figs 2-5. ‒ Kramp, 1926: 245, fig. 1. – Kramp, 1933: 571, fig. 35. – Kramp, 1959: 144, fig. 177. – Kramp, 1961: 152. – Cornelius, 1995: 134, fig. 29. Calycella producta G.O. Sars, 1874: 118, pl. 5 figs 6-8. ‒ Hincks, 1874: 134. ‒ Verrill, 1879: 17. ‒ Storm, 1879: 26. ‒ Broch, 1907: 7. Lovenella producta . ‒ Segerstedt, 1889: 12. ‒ Jäderholm, 1909: 79. ‒ Kramp, 1935: 140, fig. 57E. ‒ Fraser, 1944: 175, pl. 31 fig. 149. ‒ Schuchert, 2000: 423. ‒ Schuchert, 2001: 54, fig. 39. Campanulina producta . ‒ Bonnevie, 1899: 73. ‒ Bonnevie, 1901: 10. ‒ Broch, 1903: table. ‒ Stechow, 1922: 146. not Lovenella producta . ‒ Fraser, 1911: 44, pl. 3 figs 7-10. ‒ Fraser, 1914: 159, pl. 18 fig. 64. [in part Egmundella gracilis Stechow, 1921] not Lovenella producta . ‒ Fraser, 1937: 96, pl. 19 fig. 102. ? Opercularella producta . ‒ Vervoort, 1966: 111, fig. 12a. ‒ Vervoort, 1985: 279. Egmundella producta . ‒ Schuchert, 2016a: 219, figs 1A-D, 2A- C, 3A-F. Type localities: The syntypes of Egmundella producta came from Bodø and the Lofoten (Norway). The type locality of Cyclocanna welshi is in the North-West Atlantic, off Viriginia, USA, 37.4705°N 74.4214°W, 0-140 m. References: For the medusa see Cornelius (1995), for the hydroid see Schuchert (2016). Published as part of Peter Schuchert, Aino Hosia & Lucas Leclère, 2017, Identification of the polyp stage of three leptomedusa species using DNA barcoding, pp. 167-182 in Revue suisse de Zoologie 124 (1) on page 177, DOI: 10.5281/zenodo.322675